National survey of mentorship in Canadian general surgery residency programs: Where are we and what do we need? - Delisle, Megan; Rivard, Justin; Hebbard, Pamela; McCarthy, Brendan; Wirtzfeld, Debrah (Canadian Medical Education Journal, 2017)
Background: The benefits of mentorship on residents are well established. The current state of mentorship in General Surgery (GS) residency programs in Canada is unknown. The objectives of this study were to obtain GS residents’ and program directors’ (PD) perspectives on resident mentorship. Study Design: An electronic survey was developed and distributed to all 601 GS residents in Canada. All 17 PDs were invited for telephone interviews. Results: A total of 179 of the 601 residents responded. Ninety-seven percent (n=173) felt mentorship was important. Only 67% (n=116) identified a mentor and only 53% (n=62) reported a mentorship program. Most who identified a mentor (n=87/110, 79%) were satisfied with the mentorship received. Significant variations in mentorship existed between demographic subgroups and mentorship program types. Overall, residents (n=121, 74%) favoured having a required mentorship program. A total of 11 out of 17 PDs participated in the telephone interviews. The majority of PDs (n=9, 82%) were satisfied with current resident mentorship but most acknowledged that barriers exist (n=8, 73%). Conclusion: GS programs in Canada should ensure they are providing equal opportunities for mentorship across demographic subgroups. Programs are encouraged to examine both their program’s and their residents’ needs as well as local barriers to improve mentorship.